Question
upstudy study bank question image url

Without the use of tables or a calculator prove that \( \frac{1-\cos 2 A}{\sin 2 A}=\tan A \)

Ask by Lawson Pena. in South Africa
Feb 28,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( \frac{1 - \cos 2A}{\sin 2A} = \tan A \)

Solution

To prove that (1 - cos 2A) / (sin 2A) = tan A without using tables or a calculator, we can use the double-angle identities for sine and cosine. Step 1: Recall the double-angle identities:   • cos 2A = 1 - 2 sin² A   • sin 2A = 2 sin A cos A Step 2: Substitute the identity for cos 2A into the numerator:   1 - cos 2A = 1 - (1 - 2 sin² A) = 2 sin² A Step 3: Now, substitute these into the given expression:   (1 - cos 2A) / (sin 2A) = (2 sin² A) / (2 sin A cos A) Step 4: Simplify the fraction by canceling the common factor of 2:   = (sin² A) / (sin A cos A) Step 5: Cancel one sin A from the numerator and denominator (assuming A is not such that sin A = 0):   = sin A / cos A = tan A Thus, we have shown that (1 - cos 2A) / (sin 2A) is indeed equal to tan A.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To prove the equation \( \frac{1 - \cos 2A}{\sin 2A} = \tan A \), we can start by using some trigonometric identities. First, recall the double angle formulas: 1. \( \cos 2A = 1 - 2\sin^2 A \) 2. \( \sin 2A = 2\sin A \cos A \) Now, substitute the formula for \( \cos 2A \) into the left-hand side of the equation: \[ 1 - \cos 2A = 1 - (1 - 2\sin^2 A) = 2\sin^2 A \] So now, the left-hand side becomes: \[ \frac{1 - \cos 2A}{\sin 2A} = \frac{2\sin^2 A}{\sin 2A} \] Next, we can substitute \( \sin 2A \) with \( 2\sin A \cos A \): \[ \frac{2\sin^2 A}{\sin 2A} = \frac{2\sin^2 A}{2\sin A \cos A} \] The \( 2 \) in the numerator and denominator cancels out: \[ \frac{2\sin^2 A}{2\sin A \cos A} = \frac{\sin^2 A}{\sin A \cos A} \] Now, we can simplify this further: \[ \frac{\sin^2 A}{\sin A \cos A} = \frac{\sin A}{\cos A} \] Recognizing this fraction gives us: \[ \frac{\sin A}{\cos A} = \tan A \] Thus, we conclude that: \[ \frac{1 - \cos 2A}{\sin 2A} = \tan A \] This completes the proof.

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy